Political Institutions, Policymaking, and Economic Policy in Latin America - Martin Ardanaz; Carlos Scartascini; Mariano Tommasi (Inter-American Development Bank (IDB), 2010)
This paper surveys selected themes in the political economy of policymaking in Latin America, with an emphasis on recent research focusing on actual decision and implementation processes, and on the political institutions and state and social actors involved in those processes. In particular, the paper addresses how political rules work for or against intertemporal cooperation among political actors. The document shows that the extent to which polities obtain the key policy features that seem to determine development depends on the workings of political institutions, which define how the policymaking game is played, on the characteristics of the arenas of interaction, which define where the policymaking game is played, and on certain characteristics of key socioeconomic groups, which define who interacts with professionalpoliticians in pursuing different policy preferences.
Keywords: D72; D78; H10; H50; O10; 330; Political institutions; Public policies; Economic policy; Government capabilities; Development; Latin America